Aeroelastic behaviour of the turbine blade row in 3D viscous flow - Gnesin, V. I.; Kolodiazhnaya, L. V.; Rzadkowski, R. (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2018)
This paper presents the results of a numerical analysis of the aeroelastic behaviour of the oscillating blade row of a turbine stage in the 3D flow of viscous gas, taking into account the non-uniform pressure distribution in the circumferential direction behind the blade rotor. The numerical method is based upon the solution of the coupled problem of the unsteady aerodynamics and blade elastic oscillations in the unsteady spatial gas flow through the blade row of the axial turbine last stage. 3D viscous gas flow through the turbine stage with periodicity on the whole annulus is described by the unsteady Navier-Stokes equations in the form of conservation laws, which are integrated using the explicit monotonous finite-volume Godunov-Kolgan  difference scheme and a  moving hybrid H-O grid. The dynamic analysis uses a modal approach and 3D finite element model of a blade. The investigations showed that the unsteady pressure distribution in the circumferential direction affects the unsteady loads and modes of blade oscillations. The presented method for solving the coupled aero-elastic problem makes it possible to predict the amplitude-frequency spectrum of blade oscillations in gas flow including the forced oscillations and self-excited oscillations (flutter or auto-oscillations).